Spatiotemporal characteristics and change of cultivated land pressure in Jiangsu Province - ZHANG Zhongqi, SHEN Zhengping (Ziyuan Kexue, 2023)
[Objective] Jiangsu Province is an important area for food production in the southeastern coastal provinces of China. [Methods] With the continuous development of industrialization and urbanization and potential population growth, the conflict between population and cultivated land in the province will become very tense. It is necessary to strengthen the research on cultivated land pressure. In this study, the cultivated land pressure index (CLPI) model, Thiel index, and grey model were used to analyze the temporal and spatial characteristics and influencing factors of cultivated land pressure in Jiangsu in five years since 2000, and to predict the situation for 2025 and 2030. [Results] The results show that: (1) The CLPI of the province is between 0.94 and 1.07, which is generally in the early-warning pressure level. The Theil index of the CLPI in the province showed an increasing trend, and the city-level variation of CLPI was increasing. There is a great imbalance between Southern, Central, and Northern Jiangsu, and the CLPI decreases rapidly from south to north. (2) Among the influencing factors of cultivated land pressure, per capita food production, per capita cultivated land, and grain yield per unit area have reached a very significant level, among which per capita food production played a decisive role in determining cultivated land pressure. It indicates that per capita food production is the key variable of grain production in Jiangsu Province under the condition that other factors are relatively stable. (3) Trend analysis showed that the CLPI of the whole province will slowly decrease but remain in the early-warning pressure area in 2025 and 2030. [Conclusion] The CLPI of Wuxi and Changzhou Cities will increase rapidly, and CLPI will decline to varying degrees in other cities.